PRODUKSI DAN DAYA TERIMA CHEESE SPREAD ANALOGUE BERBAHAN BAKU SOFT TOFU DAN PAPRIKA POWDER - shifa atiyatul hasanah; Anna Mardiana Handayani (Jurnal Fakultas Teknik Kuningan, 2022)
Soybean is an important raw material in meeting the nutritional needs of the community which has a fairly high content of vegetable protein at a relatively low price. Soybean seed protein content of approximately 35%, 15% fat and minerals. Based on data from the Ministry of Industry in 2015, the average soybean consumption per person in Indonesia has increased, in 2010 it was 907,031 tons/year, in 2014 it was 954,997 tons/year. 2015 as many as 963,183 tons/year.The purpose of this study was to determine the acceptability of the cheese spread analogue using Design Expert version 10.0, the d-optimal method based on the response of color, aroma, taste and spreadability. The results of the study of the selected cheese spread analogue, namely formula 2 with a percentage of 35% soft tofu raw materials and 5% paprika powder, the acceptability was tested by 15 expert panelists with a response to color, aroma, taste and spreadability.